Transforming professional learning and practice in assessment: The triple H framework. Invited keynote address - Poskitt JM (Massey University)
Every teacher wants to be an effective educator - having positive relationships with, and enabling, students to become enthusiastic and capable learners. Teaching is demanding of the whole person – particularly the heart (being an inclusive, caring, enthusiastic and ethical person; passionate about learners and learning), the head (such as knowledge of the theory of pedagogy, curriculum and content knowledge, assessment, human development etc.), and the hands (being a highly skilled practitioner). These three determinants: the head, heart and hands are integral components, the author argues, of the triple H framework for effective, holistic professional learning. Successful professional learning needs to encompass and nourish all three determinants (head, heart and hands) for teachers. This triad notion might also be applied at the education system level by strengthening and connecting parallel components. The system heart (being the students/schools and their communities), the system hand (being PD facilitators; colleagues) and the system head (government, Ministry of Education, policy makers; researchers), all interdependently linked. We return to system aspects later in the paper. It is important to acknowledge that while all educators have much in common (for starters, each having a head, heart and most having hands; and wanting the best for their students) they have individual personalities and come from varied cultural, educational and professional backgrounds. Moreover, educators work in a variety of contexts, and typically in less than ideal professional learning circumstances particularly in relation to available time, resources and competing expectations. Professional learning (PL) is complex, yet because students deserve the best possible education, PL needs to respond to different contexts and circumstances. What is professional learning? Professional development (PD) was the previous term used. PD was conceptualised in accordance with the prevailing views about learning: transmission approaches from experts to teachers – manifested in attendance at one-off workshops or courses outside of the school. Sometimes these courses made a difference (if the timing of them and their topics happened to meet the content or pedagogical needs of the teacher). However, knowledge gained from such opportunities rarely translated into sustained classroom practice. PD was often: short term, done ‘to us by others’, characterised by individual one-off courses, one size fits all, and oriented towards improving skills and procedural knowledge (Easton, 2008). No time was allocated for reflection and feedback. Teachers were isolated since other colleagues were not privy to the same knowledge and experiences. Relentless pressure from the day to day realities of the classroom and few opportunities to re-visit professional ideas meant when difficulties were encountered in implementation, or teachers were exposed to the next wave of ideas, the new skill or notions were abandoned. With the influence of socio-cultural perspectives about learning and other societal changes the term changed to professional learning (PL). Professional learning (PL) views the teacher as a learner with their own values, beliefs and content needs; capable of self-ownership and ongoing responsibility for their learning; and, in accordance with adult learning principles, needing a balance between individual and collaborative learning. Knowledge is viewed as dynamic, iterative, co-constructed in response to cultural and contextualised interactions – hence PL is largely school-based. Deeper learning necessitates extended time and opportunities to learn (Timperley et al., 2007). Developing from a novice to an expert (teacher) requires movement from reliance on procedural rules and routines to a theorised and principled-based, integrated competency. Expert competency encompasses a holistic view, and capability in being responsive, flexible and fluid in solving problems. Informing and deepening professional’s educational values and beliefs requires commitment and inevitably challenges individual’s identity and professional motivation (Timperley et al., 2007, p.13). This is why I argue deep, effective professional learning for teachers needs a head, heart and hands framework. Both the head and the heart are essential for life; so it may be arbitrary as to which determinant on which to focus first. Adults differ as to whether they need to be cognitively or emotionally triggered to engage with ideas, but to grapple deeply with ideas requires both cognitive and emotional engagement. Initial attention is often gained from emotional connections so the heart PL elements will be explored first. This paper examines three questions through the proposed triple H framework: • What does the research literature reveal about effective professional learning in assessment? • What impact does PL have on professional practice? • What are the implications at policy, system, school and teacher level?
Keywords: assessment for learning; professional learning; policy; framework